PENGARUH AKUPRESURE PC 6 (Pericardium 6) TERHADAP DERAJAT EMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER I DI POSKESDES MARGO MULYO 20 KABUPATEN BANYUASIN - Sepiwiryanti, Wika; Andreinie, Ria; Putri, Vivi Dwi; Apriyanti, Nora Dwi (STIKES Abdurahman. Pusat Informasi dan Manajemen, 2026)
During pregnancy, women will experience various changes that will occur psychologically and physiologically, causing discomfort. Emesis gravidarum is caused by increased estrogen, progesterone, and the release of human chorionic gonadotropin placenta, causing nausea and vomiting. Handling nausea and vomiting during pregnancy can be done through non-pharmacological measures, namely using acupressure therapy. The purpose of this study was to determine the effect of giving PC 6 (Pericardium 6) acupressure on emesis gravidarum in pregnant women in the first trimester at the Margo Mulyo 20 Health Post, Banyuasin Regency. The research sample was pregnant women with emesis gravidarum at the Margo Mulyo 20 Health Post, with as many as 20 respondents. The research design used a pretest-posttest with a control group design. The results of the analysis showed that giving PC 6 (Pericardium 6) acupressure had an effect on reducing emesis gravidarum in pregnant women in the first trimester with a p-value = 0,002.